The National Library of Medicine’s Disaster Information Management Research Center - Phillips, Steven J. (Frontiers in Public Health, 2013)
The Disaster Information Management Research Center (DIMRC) develops and provides access to health information resources and technology for disaster preparedness, response, and recovery. DIMRC focuses on maintaining access to health information at all phases of disasters, developing innovative products and services for emergency personnel, conducting research to support disaster health information management, and collaborating with other agencies and communities. Several tools are available to help emergency responders in hazardous materials or Chemical, Biological, Radiological, or Nuclear incidents. Access to the literature is made available through PubMed and the Resource Guide for Disaster Medicine and Public Health, with links to online documents and resources from numerous organizations and government agencies. In addition, DIMRC supports the Disaster Information Specialist Program, a collaborative effort to explore and promote the role of librarians and information specialists in the provision of disaster-related information resources to the workforce and communities.